2015
DOI: 10.1038/cmi.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of CD180 inhibits IFN-α signaling in a Lyn-PI3K-BTK-dependent manner in B cells

Abstract: A hallmark of systemic lupus erythematosus (SLE) is the consistent production of various auto-antibodies by auto-reactive B cells. Interferon-a (IFN-a) signaling is highly activated in SLE B cells and plays a vital role in the antibody response by B cells. Previous studies have shown that CD180-negative B cells, which are dramatically increased in SLE patients, are responsible for the production of auto-antibodies. However, the association between CD180 and IFN-a signaling remains unknown. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…Interestingly, we also found that anti-CD180 stimulation downregulated the mRNA expression of CD180, strengthening the possibility of autoregulation of CD180 expression by B cells. Signaling via TLRs can interfere with CD180 signals, since ligands of TLR7 and TLR9 have already been shown to downregulate CD180 expression in human peripheral blood B cells [16]. Nevertheless, according to our results, co-treatment with anti-CD180 and CpG reduced the expression of CD180 to a similar level as anti-CD180 did on its own, while CpG treatment alone had no significant effect on the expression of CD180.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Interestingly, we also found that anti-CD180 stimulation downregulated the mRNA expression of CD180, strengthening the possibility of autoregulation of CD180 expression by B cells. Signaling via TLRs can interfere with CD180 signals, since ligands of TLR7 and TLR9 have already been shown to downregulate CD180 expression in human peripheral blood B cells [16]. Nevertheless, according to our results, co-treatment with anti-CD180 and CpG reduced the expression of CD180 to a similar level as anti-CD180 did on its own, while CpG treatment alone had no significant effect on the expression of CD180.…”
Section: Discussionsupporting
confidence: 48%
“…The CD180-negative B cells were described as highly activated cells in SLE [11], and stimulation via CD180 is known to activate B cells [6]. Furthermore, TLR ligands were reported to downregulate the mRNA expression of CD180 molecule [16], thus we hypothesized that the decreased CD180 expression of dcSSc B cells could be a result of activation through TLRs. To investigate whether TLR stimulation leads to diminished expression of CD180 molecules in B cells, we stimulated tonsillar B cells with anti-CD180 antibody.…”
Section: Tlr Ligation Results In Reduced Cd180 Mrna and Protein Exprementioning
confidence: 95%
“…Our previous study and others have reported that the percentage of CD180-negative B cells is dramatically increased in PBMCs from SLE patients ( 32 , 33 ). However, the mode of CD180 expression on monocytes and DCs in SLE patients is still unknown.…”
Section: Resultsmentioning
confidence: 69%
“…Our previous study and others have reported that ligation of CD180 can activate Lyn and subsequently induce the activation of downstream signaling pathways ( 28 , 32 ). To gain mechanistic insight into how CD180 ligation leads to the phosphorylation of SHP-1 and SHP-2, we next investigated whether CD180 induced the phosphorylation of SHP-1 and SHP-2 through Lyn.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation